Common Presence of Phototrophic Gemmatimonadota in Temperate Freshwater Lakes - Mujakić, Izabela; Andrei, Adrian-Ştefan; Shabarova, Tanja; Fecskeová, Lívia Kolesár; Salcher, Michaela M; Piwosz, Kasia; Ghai, Rohit; Koblížek, Michal (mSystems, 2021)
Members of the bacterial phylum Gemmatimonadota are ubiquitous in most natural environments and represent one of the top 10 most abundant bacterial phyla in soil. Sequences affiliated with Gemmatimonadota were also reported from diverse aquatic habitats; however, it remains unknown whether they are native organisms or represent bacteria passively transported from sediment or soil. To address this question, we analyzed metagenomes constructed from five freshwater lakes in central Europe. Based on the 16S rRNA gene frequency, Gemmatimonadota represented from 0.02 to 0.6% of all bacteria in the epilimnion and between 0.1 and 1% in the hypolimnion. These proportions were independently confirmed using catalyzed reporter deposition-fluorescence in situ hybridization (CARD-FISH). Some cells in the epilimnion were attached to diatoms (Fragilaria sp.) or cyanobacteria (Microcystis sp.), which suggests a close association with phytoplankton. In addition, we reconstructed 45 metagenome-assembled genomes (MAGs) related to Gemmatimonadota They represent several novel lineages, which persist in the studied lakes during the seasons. Three lineages contained photosynthesis gene clusters. One of these lineages was related to Gemmatimonas phototrophica and represented the majority of Gemmatimonadota retrieved from the lakes' epilimnion. The other two lineages came from hypolimnion and probably represented novel photoheterotrophic genera. None of these phototrophic MAGs contained genes for carbon fixation. Since most of the identified MAGs were present during the whole year and cells associated with phytoplankton were observed, we conclude that they represent truly limnic Gemmatimonadota distinct from the previously described species isolated from soils or sediments.IMPORTANCE Photoheterotrophic bacterial phyla such as Gemmatimonadota are key components of many natural environments. Its first photoheterotrophic cultured member, Gemmatimonas phototrophica, was isolated in 2014 from a shallow lake in the Gobi Desert. It contains a unique type of photosynthetic complex encoded by a set of genes which were likely received via horizontal transfer from Proteobacteria We were intrigued to discover how widespread this group is in the natural environment. In the presented study, we analyzed 45 metagenome-assembled genomes (MAGs) that were obtained from five freshwater lakes in Switzerland and Czechia. Interestingly, it was found that phototrophic Gemmatimonadota are relatively common in euphotic zones of the studied lakes, whereas heterotrophic Gemmatimonadota prevail in deeper waters. Moreover, our analysis of the MAGs documented that these freshwater species contain almost the same set of photosynthesis genes identified before in Gemmatimonas phototrophica originating from the Gobi Desert.
Keywords: CARD-FISH; freshwater ecology; aquatic bacteria; anoxygenic phototrophs; metagenome; photosynthesis gene cluster; Gemmatimonadota; MAGs; Gemmatimonadetes